Current and emerging trends in bioremediation of petrochemical waste: A review - Singh P.; Jain R.; Srivastava N.; Borthakur A.; Pal D.B.; Singh R.; Madhav S.; Srivastava P.; Tiwary D.; Mishra P.K. (My University, 2025)
Various industries release harmful petrochemical contaminants into the environment. To treat these petrochemical contaminants at source, different physical, chemical, and biological methods have been proposed and applied worldwide. However, physical and chemical methods have their own advantages and limitations; in this review, we majorly focused on the biodegradation of petrochemical wastes. First, a background study on the literature available in this field is presented. Second is a review of the toxic effects of petrochemical waste and various physical and chemical processes, followed by elaborate biological processes available for petrochemical waste degradation. Further, different aspects of bioremediation, such as modes, factors, limitations, and future perspectives are critically reviewed and presented. It was found that most of the studies performed on bioremediation of petrochemical waste employed bacteria for the degradation purpose. Some studies also made use of algae, fungi, yeast, genetically modified organisms, biosurfactants, or a consortium of these microbes. Moreover, use of bioremediation is still limited at field scale due to certain limitations, which have been elaborated in this article. Overall, we strongly believe that with bioremediation capturing the attention of environmentalists worldwide, there is still a prevailing need to scale up from lab to land level applications and adaptations. © 2017 Taylor & Francis Group, LLC.